The reactome pathway knowledgebase 2022. Issue Volume 50:Issue D1(2022) (12th November 2021) - Gillespie, Marc; Jassal, Bijay; Stephan, Ralf; Milacic, Marija; Rothfels, Karen; Senff-Ribeiro, Andrea; Griss, Johannes; Sevilla, Cristoffer; Matthews, Lisa; Gong, Chuqiao; Deng, Chuan; Varusai, Thawfeek; et al.
Abstract: The Reactome Knowledgebase (https://reactome.org ), an Elixir core resource, provides manually curated molecular details across a broad range of physiological and pathological biological processes in humans, including both hereditary and acquired disease processes. The processes are annotated as an ordered network of molecular transformations in a single consistent data model. Reactome thus functions both as a digital archive of manually curated human biological processes and as a tool for discovering functional relationships in data such as gene expression profiles or somatic mutation catalogs from tumor cells. Recent curation work has expanded our annotations of normal and disease-associated signaling processes and of the drugs that target them, in particular infections caused by the SARS-CoV-1 and SARS-CoV-2 coronaviruses and the host response to infection. New tools support better simultaneous analysis of high-throughput data from multiple sources and the placement of understudied ('dark') proteins from analyzed datasets in the context of Reactome's manually curated pathways.